Pengaruh Kompetensi dan Disiplin Kerja terhadap Produktivitas Kerja Pegawai ASN pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Bekasi - Chintya Alfitriani; Usran Masahere; Asep Asep (Pusat Riset dan Inovasi Nasional, 2025)
Improving the quality of human resources is crucial in realizing effective, professional, and responsible public services, especially in government agencies. The work productivity of State Civil Apparatus (ASN) employees is influenced by various factors, including competence and work discipline. This study aims to analyze the influence of competence and work discipline on the work productivity of ASN employees at the Bekasi City Personnel and Human Resources Development Agency (BKPSDM). This study has a population of 60 ASN employees. Using the Slovin formula and a margin of error of 5% (0.05), the number of samples used was 53 respondents. The research method used is a quantitative approach with statistical analysis techniques to test the relationship between variables. The results showed that partially, competence and work discipline each had a positive and significant effect on work productivity, with the calculated t values of 4.203 and 4.449 respectively greater than the t table of 2.009, and significant at the level of < 0.001 (less than 0.05). Simultaneously, the results of the F test showed that the F value of 73.627 was greater than the F of table 3.18. Thus, competence and work discipline together have a positive and significant effect on the work productivity of ASN employees at the Bekasi City BKPSDM